Electromagnetic fields and radiation human bioeffects and safety - Habash, Riadh W. Y. (Marcel Dekker, 2002)
Explores the sources, characteristics, bioeffects, and health hazards of extremely low-frequency (ELF) fields and radio frequency radiation (RFR). This title discusses electromagnetic (EM) interaction mechanisms in biological systems as well as the impact of EM fields on free radicals, cells, tissues, organs, whole organisms, and the population.